Loneliness, Loss, and the Search for Belonging: An Interpretive Qualitative Study of Older Adults Experiencing Homelessness - Aisyah Febrianti Kusmiandini; Nuke Martiarini (Journal of Educational, Health and Community Psychology, 2026)
Homelessness among older adults is a complex relational phenomenon shaped by social disconnection and weakened family ties, which can intensify loneliness, experiences of loss, and a diminished sense of belonging. This study examined how older adults experiencing homelessness interpret and cope with loneliness in everyday life, and how they (re)construct a sense of “home” despite profound material and social constraints. Using an interpretive qualitative design, we conducted observations, semi-structured interviews, and photovoice with three older adults experiencing homelessness in Semarang. Data were analyzed using Reflexive Thematic Analysis to foreground participants’ meaning-making processes. Four themes were generated: (1) loss of family intimacy, (2) disappointment and acceptance as emotional negotiation, (3) animals and personal objects as substitute attachment figures providing comfort and emotional security, and (4) home-making as an active process of creating familiarity and comfort through resting spaces, family photographs, personal belongings, and other symbolic connections. Overall, participants demonstrated adaptive emotional coping and constructed meaningful, albeit precarious, spaces of belonging. These findings indicate that services should address emotional and relational needs alongside material support. Community-based responses could facilitate social reconnection, grief-informed support, and opportunities for symbolic home-making that affirm identity and attachment. Policies should recognize the psychological value of personal belongings and companion animals as resources for stability. Future research should involve larger, more diverse samples and participatory methods to strengthen the transferability and practical relevance of interventions for older adults experiencing homelessness.